Internationalizing your campus : fifteen steps and fifty Federal grants to success - Burr, Patricia L. (Contemporary perspectives on grants and institutional advancement., 2004)
This book is about getting organized, establishing clarity of thought, following the guidelines, and taking care to get the application right the first time. Accomplishing those steps can lead to funding. It is also about matching the campus mission to the grant's legislative intent. Some sample steps described in the book include 1. The needs analysis on campus (why does the campus need this funding) 2. The trip to Washington, DC (to meet the professionals in charge of the program and to read proposals that have been recently funded under the grant program) 3. The formation of a work group (there will be multiple grant benefi- ciaries, therefore, there should be multiple workers in the applicationprocess) 4. The insight into how to manage the funding when it is received (now, what was it that I said I would do if this proposal were funded?) And, while this book is written to help you find and secure funding to reach international campus goals, the process applies to a wide variety of grant-funding opportunities. The steps are essentially the same in competitive grant cycles of many federal agencies.